6a-9=a+46

Simple and best practice solution for 6a-9=a+46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-9=a+46 equation:


Simplifying
6a + -9 = a + 46

Reorder the terms:
-9 + 6a = a + 46

Reorder the terms:
-9 + 6a = 46 + a

Solving
-9 + 6a = 46 + a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
-9 + 6a + -1a = 46 + a + -1a

Combine like terms: 6a + -1a = 5a
-9 + 5a = 46 + a + -1a

Combine like terms: a + -1a = 0
-9 + 5a = 46 + 0
-9 + 5a = 46

Add '9' to each side of the equation.
-9 + 9 + 5a = 46 + 9

Combine like terms: -9 + 9 = 0
0 + 5a = 46 + 9
5a = 46 + 9

Combine like terms: 46 + 9 = 55
5a = 55

Divide each side by '5'.
a = 11

Simplifying
a = 11

See similar equations:

| 57=15-6x | | 3r+24/9=5r-30/5 | | 1/3(12p+9)-(p-4) | | 4x/3(2x-4)=48 | | 3x-37=14 | | 1/2(12p+9)-(p-4) | | 3v+29=5v+7 | | 7x+6=26 | | 23-6x=-37 | | 2x+4(10-x)=28 | | -5x+2=-4(2y+4) | | 8n+62=13n+2 | | -7x-34=64 | | -9/4+8 | | 3x+12=93-6 | | -6x-16=-82 | | c+25=3c+1 | | -11+4x=19+2x | | 3/4*-3 | | -36-5=9-10x | | 90-7x= | | 9x-5(x-12)=30 | | 3/4*3 | | 3x+22=12x-58 | | 3x-8=x-8 | | 110-12x=266 | | 8x+9a-7b+9b-3a+12x= | | (7x+33)=(11x+21) | | 6x+35=15x-35 | | -31-3x=-73 | | x/9-x/10=11 | | 4x-3=14-73 |

Equations solver categories